2021
DOI: 10.31234/osf.io/xye8u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How WEIRD is CHI?

Abstract: Computer technology is often designed in technology hubs in Western countries, invariably making it “WEIRD”, because it is based on the intuition, knowledge, and values of people who are Western, Educated, Industrialized, Rich, and Democratic. Developing technology that is universally useful and engaging requires knowledge about members of WEIRD and non-WEIRD societies alike. In other words, it requires us, the CHI community, to generate this knowledge by studying representative participant samples. To find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…When answering RQ2, 94% of the 85 papers were conducted solely or mostly on participants from North America and Europe (see Table 2). This mirrors a long-running trend in HCI research, with 73% of CHI studies from 2016-2020 recruiting participants from nations with less than an eighth of the world's population [85]. Our review of papers across a range of HAI and HCI venues shows that this effect is even more pronounced in voice assistant research.…”
Section: Whose Voices Are Heard In Va Research?mentioning
confidence: 52%
“…When answering RQ2, 94% of the 85 papers were conducted solely or mostly on participants from North America and Europe (see Table 2). This mirrors a long-running trend in HCI research, with 73% of CHI studies from 2016-2020 recruiting participants from nations with less than an eighth of the world's population [85]. Our review of papers across a range of HAI and HCI venues shows that this effect is even more pronounced in voice assistant research.…”
Section: Whose Voices Are Heard In Va Research?mentioning
confidence: 52%
“…2 But what about research? An analysis of CHI papers from 2016-2020 found that 73% of CHI studies recruited Western participant samples representing less than 12% of the world's population; this reflects the organisations that submit to CHI, as over 80% of papers used participants from the country of authors' institutions [14]. Inspired by this we have previously investigated these issues in the context of voice assistants and found a similar story.…”
mentioning
confidence: 87%